Misusing Elastics for Midline Diastema Closure - Disaster and Treatment Via a Case Report in Vietnam - Ngoc, Vo Nhu Truong; Huan, Ly Van; Loan, Hoang Kim; Hung, Dang Trieu; Dong, Ta Thanh (Journal of Dentistry Indonesia, 2023)
Midline diastema has been a popular aesthetic problem for children. Several treatment options are available, however, the use of elastic bands without other appliances for closing the diastema still remains a pressing issue in Vietnam, which could be done by the patient’s parents either themselves or under the dental practitioners’ suggestion. Objective: To report a specific case about the extensive extrusion regarding upper central incisors in a pediatric patient due to misusing the elastic band, in which management was complex due to an unfavorable situation for splinting. Case Report: Single rubber band usage for orthodontic movement in closing diastema has been an unresolved disaster in Vietnam, leading to the need for early diagnosis and immediate intervention when facing the complications. Conclusion: Significant information dissemination is paramount for long-term improvement in the oral health of pediatric patients in Vietnam and around the world. Key words: bite-raising technique, diastema, palatal expansion technique, rubber band, tooth